2015
DOI: 10.1158/0008-5472.can-14-1254
|View full text |Cite
|
Sign up to set email alerts
|

miR-21 Inhibition Reduces Liver Fibrosis and Prevents Tumor Development by Inducing Apoptosis of CD24+ Progenitor Cells

Abstract: MiR-21 is upregulated in hepatocellular carcinoma and intrahepatic cholangiocarcinoma where it is associated with poor prognosis. Here we offer preclinical evidence that miR-21 offers a therapeutic and chemopreventive target in these liver cancers. In mice with hepatic deletion of Pten, anti-miR-21 treatment reduced liver tumor growth and prevented tumor development. These effects were accompanied with a decrease in liver fibrosis and a concomitant reduction of CD24+ liver progenitor cells and S100A4+ cancer-a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 40 publications
0
74
3
Order By: Relevance
“…In the liver, OPN has been shown to modulate regeneration, inflammation and fibrosis and more recently, to induce dedifferentiation of hepatocytes (37,38). Our group has also shown that OPN is necessary for the survival of CD24 + liver progenitor cells (39). Both dedifferentiation of hepatocytes and accumulation of CD24 + cells have been proposed as early events in HCC tumor initiation (40,41).…”
Section: Discussionmentioning
confidence: 94%
“…In the liver, OPN has been shown to modulate regeneration, inflammation and fibrosis and more recently, to induce dedifferentiation of hepatocytes (37,38). Our group has also shown that OPN is necessary for the survival of CD24 + liver progenitor cells (39). Both dedifferentiation of hepatocytes and accumulation of CD24 + cells have been proposed as early events in HCC tumor initiation (40,41).…”
Section: Discussionmentioning
confidence: 94%
“…Both plastic stents and self-expandable metallic stents can be utilized, but self-expandable metallic stents seem to offer several advantages, including higher patency duration than plastic stents 264 . 267,268 and fusion genes 68,74,79,269 . Targeted anti-fibrotic therapy is also under investigation 183 .…”
Section: Biliary Stentingmentioning
confidence: 99%
“…For example, increased miR-21 expression might play an important role in liver fibrosis, consistent with previous studies examining the role of miR-21 in kidney, heart and lung fibrosis 15–20. In cholangiocarcinoma and HCC, miR-21 is upregulated, thereby inhibiting the expression of crucial tumour suppressors and favouring hepatic cells survival 19 21–24 . miR-21 also regulates early phases of liver regeneration following partial hepatectomy 25 26.…”
Section: Introductionmentioning
confidence: 99%